2013
DOI: 10.1103/physrevlett.110.210501
|View full text |Cite
|
Sign up to set email alerts
|

Catch-Disperse-Release Readout for Superconducting Qubits

Abstract: We analyze a single-shot readout for superconducting qubits via the controlled catch, dispersion, and release of a microwave field. A tunable coupler is used to decouple the microwave resonator from the transmission line during the dispersive qubit-resonator interaction, thus circumventing damping from the Purcell effect. We show that if the qubit frequency tuning is sufficiently adiabatic, a fast high-fidelity qubit readout is possible even in the strongly nonlinear dispersive regime. Interestingly, the Jayne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 28 publications
1
44
0
Order By: Relevance
“…To the best of our knowledge this state was first described in Ref. [10]. Schematic diagrams of the dressed coherent states |g, α and |e, α for |α| (20), and highlight the fact that the dressed coherent state has the same distribution of superposition coefficients as the coherent state, only for the dressed states instead of the bare states.…”
Section: A Analytic Derivationmentioning
confidence: 93%
See 1 more Smart Citation
“…To the best of our knowledge this state was first described in Ref. [10]. Schematic diagrams of the dressed coherent states |g, α and |e, α for |α| (20), and highlight the fact that the dressed coherent state has the same distribution of superposition coefficients as the coherent state, only for the dressed states instead of the bare states.…”
Section: A Analytic Derivationmentioning
confidence: 93%
“…In this manuscript, we will show that in the lab frame of the experiment a more accurate description of the joint state is the dressed coherent state |g/e, α [10]. Unlike the description in the dispersive frame, the dressed coherent state of the lab frame is entangled, even if the qubit is not initially in a superposition state.…”
mentioning
confidence: 93%
“…In particular, it can be shown that a nonlinear resonator near the bifurcation point at large photon numbers is equivalent to a degenerate parametric amplifier driven with a detuned pump [33]. Squeezed states can be used to improve measurement accuracy [34,35] in a range of applications, such as gravitational wave detectors [36], superconducting qubit readout [37][38][39][40][41][42], and nano/micromechanical position measurement [11,43,44]. There is currently a significant experimental interest in producing squeezed microwave states with Josephson parametric amplifiers [21,[45][46][47][48][49]; the self-developing squeezing due to the nonlinearity of a microwave resonator (with revival and formation of "cat" states) has also been demonstrated experimentally [50].…”
Section: Introductionmentioning
confidence: 99%
“…A catch and release protocol for qubit readout based on the setup of Ref. [16] was already theoretically studied by Sete and co-authors [28].…”
mentioning
confidence: 99%
“…If the goal is to improve qubit readout, there is an optimal value of the modulation amplitude where the overlap between the two Wigner functions is minimal. To quantify the state discrimination, we compute the measurement error E = 1 2 dx Min[P 0 (x), P 1 (x)] [28]. In this expression, P i is the marginal of the Wigner function corresponding to |i and integrated along the imaginary axis (see Appendix E).…”
mentioning
confidence: 99%